The Effect of Competence, Organizational Culture, and Emotional Intelligence on Employee Performance on Lembaga Perkreditan Desa (LPD) in Denpasar Selatan - I Nyoman Resa Adhika; I Gede Rihayana; Putu Pradiva Putra Salain (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2022)
The purpose of this study was to determine the effect, competence, organizational culture and emotional intelligence on employee performance at LPD in South Denpasar. Quantitative methods/approaches are used in this study. The number of samples used were 87 LPD employees in South Denpasar with the saturated sampling method, namely by using all the population as samples. Collecting data using a questionnaire. The data analysis technique used multiple linear regression. Then analyzed using SPSS 23 for windows. The results showed that all the proposed research hypotheses were accepted. The conclusion in this study is that competence has a positive and significant effect on employee performance. Organizational culture has a positive and significant effect on employee performance. Emotional intelligence has a positive and significant effect on employee performance. Efforts are made to improve performance, namely providing training and opportunities to add insight to employees and develop work creativity in accordance with their fields.